Search for the critical point of strongly-interacting matter in 40Ar + 45Sc collisions at 150A Ge V /c using scaled factorial moments of protons - H. Adhikary; P. Adrich; K. K. Allison; N. Amin; E. V. Andronov; T. Antićić; I.-C. Arsene; M. Bajda; Y. Balkova; M. Baszczyk; D. Battaglia; A. Bazgir; et al. (European Physical Journal C: Particles and Fields, 2023)
Abstract The critical point of dense, strongly interacting matter is searched for at the CERN SPS in 40Ar  + 45Sc collisions at 150A  Ge V /c. The dependence of second-order scaled factorial moments of proton multiplicity distribution on the number of subdivisions of transverse momentum space is measured. The intermittency analysis is performed using both transverse momentum and cumulative transverse momentum. For the first time, statistically independent data sets are used for each subdivision number. The obtained results do not indicate any statistically significant intermittency pattern. An upper limit on the fraction of correlated proton pairs and the power of the correlation function is obtained based on a comparison with the Power-law Model developed for this purpose.